Mr. Popper's Penguins (Beverly Hills, California : Twentieth Fox, 2011)
Mr. Popper's Penguins is the story of a boy whose explorer father loves him but neglects him in favor of his career. Once the boy grows to sharkish real-estate wheeler-dealer manhood in NYC, he does the same thing to his wife, daughter, and son. Promised a partner position in his real-estate firm, he woos a reluctant seller to part with the Tavern on the Green. Life is going fine until his dad's final gift to him arrives. Then Mr. Popper's life changes radically, because the gift is penguins--live, breathing, fish-loving penguins. Mr. Popper, at first vexed and then beguiled by the creatures, tries to deal with them, his job, his children, his ex-wife, a nosy neighbor, an officious zoo guy, and the state of his soul.